2022
DOI: 10.1038/s41467-022-35641-3
|View full text |Cite|
|
Sign up to set email alerts
|

Force-tuned avidity of spike variant-ACE2 interactions viewed on the single-molecule level

Abstract: Recent waves of COVID-19 correlate with the emergence of the Delta and the Omicron variant. We report that the Spike trimer acts as a highly dynamic molecular caliper, thereby forming up to three tight bonds through its RBDs with ACE2 expressed on the cell surface. The Spike of both Delta and Omicron (B.1.1.529) Variant enhance and markedly prolong viral attachment to the host cell receptor ACE2, as opposed to the early Wuhan-1 isolate. Delta Spike shows rapid binding of all three Spike RBDs to three different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 82 publications
4
25
0
Order By: Relevance
“…41 Atomic force microscopy (AFM) studies quantified the importance of mechanical stability in mediating immune evasion, showing that a combination of mechanical forces, protein stability, and binding interactions play an important role in controlling the virus's fitness advantage and immune escape mechanisms. 42–44…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Atomic force microscopy (AFM) studies quantified the importance of mechanical stability in mediating immune evasion, showing that a combination of mechanical forces, protein stability, and binding interactions play an important role in controlling the virus's fitness advantage and immune escape mechanisms. 42–44…”
Section: Introductionmentioning
confidence: 99%
“…41 Atomic force microscopy (AFM) studies quantified the importance of mechanical stability in mediating immune evasion, showing that a combination of mechanical forces, protein stability, and binding interactions play an important role in controlling the virus's fitness advantage and immune escape mechanisms. [42][43][44] The Omicron BA.2 subvariants of SARS-CoV-2 have been associated with the increased transmissibility and vaccine evasion capacity. 45,46 Structural and biophysical studies of the RBD-ACE2 complexes for the BA.1.1, BA.2, and BA.3 variants revealed that the binding affinity of the Omicron BA.2 with ACE2 is stronger than the affinities of the BA.3 and BA.1 subvariants.…”
Section: Introductionmentioning
confidence: 99%
“…The spike-ACE2 interface exploits a number of hydrogen bonds and salt brides stabilizing it and forming two strong flanks that can resist mechanical pulling. 88 In addition to protein contacts, the interface is flanked by both host and viral glycans. The ACE2 glycosylation at site N322 was suggested to increase the overall binding strength by binding to the RBD surface.…”
Section: S1mentioning
confidence: 99%
“…At the same time, Omicron mutations S477N, T478K, E484A and K417N may induce a moderate loss in ACE2 binding while promoting the increased neutralization escape potential of the Omicron variant from antibodies [41]. Atomic force microscopy studies revealed the role of mechanical stability in mediating immune evasion, pointing to a combined effect of mechanical forces, protein stability and binding interactions that collectively control the virus fitness advantage and immune escape mechanisms [42][43][44]. The structural basis of the higher binding affinity of ACE2 to currently circulating Omicron subvariants was elucidated in an investigation which reported the structures of the RBD-ACE2 complexes for BA.1.1, BA.2, and BA.3 variants [45].…”
Section: Introductionmentioning
confidence: 99%